Differential impact of high and low penetrance TNFRSF1A gene mutations on conventional and regulatory CD4+ T cell functions in TNFR1‐associated periodic syndrome. Issue 5 (23rd November 2015) - Pucino, Valentina; Lucherini, Orso Maria; Perna, Francesco; Obici, Laura; Merlini, Giampaolo; Cattalini, Marco; La Torre, Francesco; Maggio, Maria Cristina; Lepore, Maria Teresa; Magnotti, Flora; Galgani, Mario; Galeazzi, Mauro; et al.
Abstract : Multiple variants of TNFRSF1A mutations may impact conventional and regulatory CD4 + T cell functions in TRAPS patients. Abstract : TNFR‐associated periodic syndrome is an autoinflammatory disorder caused by autosomal‐dominant mutations in TNFRSF1A, the gene encoding for TNFR superfamily 1A. The lack of knowledge in the field of TNFR‐associated periodic syndrome biology is clear, particularly in the context of control of immune self‐tolerance. We investigated how TNF‐α/TNFR superfamily 1A signaling can affect T cell biology, focusing on conventional CD4 + CD25 − and regulatory CD4 + CD25 + T cell functions in patients with TNFR‐associated periodic syndrome carrying either high or low penetrance TNFRSF1A mutations. Specifically, we observed that in high penetrance TNFR‐associated periodic syndrome, at the molecular level, these alterations were secondary to a hyperactivation of the ERK1/2, STAT1/3/5, mammalian target of rapamycin, and NF‐κB pathways in conventional T cells. In addition, these patients had a lower frequency of peripheral regulatory T cells, which also displayed a defective suppressive phenotype. These alterations were partially found in low penetrance TNFR‐associated periodic syndrome, suggesting a specific link between the penetrance of the TNFRSF1A mutation and the observed T cell phenotype. Taken together, our data envision a novel role for adaptive immunity in the pathogenesis of TNFR‐associated periodic syndrome involving both CD4 + conventional T cells and Tregs, suggesting a novel mechanism of inflammation in the context of autoinflammatory disorders.